2021
DOI: 10.3390/agriculture11070572
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Red Orange and Lemon Extract-Enriched Diet in Suckling Lambs’ Fecal Microbiota

Abstract: Red orange and lemon extract (RLE) is an anthocyanins-rich dietary supplement that may influence gastrointestinal bacterial community in ruminants. The aim of the present study was to investigate the RLE effects on gut microbiota composition in lambs. Twenty-eight lambs were randomly divided into a control group (CON; n = 14) and an anthocyanin group (ANT; n = 14) and fed the same diet; additionally, only the ANT received 90 mg/kg live weight of RLE at day. After lamb slaughter (40 ± 1 days), fecal samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The red orange and lemon extract (RLE) derived from red orange and lemon processing wastes is rich in flavanones and anthocyanins (further information is available in previous studies) [ 18 , 19 ]. Some studies have reported important improvements in the oxidative status of the muscles in kids [ 3 ] and lambs [ 20 ] fed with red orange and lemon extract (RLE), with positive effects on their intestinal microflora due to the inhibition of the growth of potentially pathogenic bacteria [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The red orange and lemon extract (RLE) derived from red orange and lemon processing wastes is rich in flavanones and anthocyanins (further information is available in previous studies) [ 18 , 19 ]. Some studies have reported important improvements in the oxidative status of the muscles in kids [ 3 ] and lambs [ 20 ] fed with red orange and lemon extract (RLE), with positive effects on their intestinal microflora due to the inhibition of the growth of potentially pathogenic bacteria [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the dietary assumption of high amounts of substances with antioxidant activity results in the transfer of these molecules to different animal tissues, usually followed by a significant increase in their total antioxidant capacity ( 55 ), and that several polyphenolic molecules in plants possess antioxidant activities ( 23 ). Research is raising interest in these compounds due to their beneficial effects on health as anticarcinogenic ( 56 ), anti-inflammatory ( 57 ), immune and microbial modulating ( 58 , 59 ), especially if taken through the diet. Several studies confirm a positive correlation between total antioxidant activity and the total phenol content assumed with diet, for example, spinach and broccoli ( 60 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Emission reductions can be achieved through improved grazing conditions, improved animal productivity, and special nutritional additives [ 29 ]. An option for such additives is anthocyanins or red–orange and lemon extracts [ 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%